Reconstruction of the Integration of Religion and Modern Sanis - Waluyo; Engku Ab Rahman, Ts. Engku Shahrulerizal Bin; Nurkhafiq, M. (LETIGES, 2025)
The meeting of modern religion and science in the 17th century, although the initial encounter seemed to be a distinct entity from philosophical and historical perspectives, was once mutually coordinated. Different paradigms of religion and science are the background of this study. This paper focuses on efforts to reconceptualise and to reconstruct the integration of Islamic education interconnections (integration of religion and science). The research was inspired by a book entitled “Merumuskan Rangka Kerja Islamisasi Ilmu Pengetahuan: Islamisasi Worldview, Paradigma dan Teori,